The Use of Mondly Applications as a Media to Increase Vocabulary and Grammar of The Seventh Grade Student at Semarang - Dwi Handayani Setyaningrum, Semia; Senowasito; Ririn Ambarini (CV. Mitkom Indotama, 2024)
Mondly app is the best language learning app that can help students build vocabulary and develop proper grammar. Results from seventh-grade students of SMP N 17 Semarang the average vocabulary pre-test score was 65.03, and the average grammar pre-test score was 65.57. The average score on the vocabulary post-test was 83.45, and the average score on the grammar post-test was 83.27. Data from SPSS 26, where the correlation coefficient calculated and analyzed by the researcher obtained a result of 0.000, was observed from the results during the pre-test to post-test period. The correlation between the pre-test and post-test results is accepted because it is less than 0.05. There is a significant difference in students'' mastery of English vocabulary and grammar before and after using the Mondly application. At the time of the research, the class atmosphere became happier and livelier.